N-Formylation of Amines Over a Protonic Zeolite Socony Mobil (H-Zsm-5) and Ion-Exchanged Zeolite: Catalytic Performance and Reusability - Yılmaz, Selahattin; Mekkas, Nadia; Azizi, Soulef; Yilmaz, Selahattin; Benbouzid, Mohammed; Dizoglu, Gunsev; Taib, Hana; Gherraf, Noureddine (Sciendo, 2025)
An efficient and sustainable method was developed for the N-formylation of primary and secondary amines using formic acid in dichloromethane at room temperature over zeolite H-ZSM-5 and ion-exchanged forms (Zn-ZSM-5, Cu-ZSM-5, Ag-ZSM-5, and Cd-ZSM-5). The catalysts were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface area, ammonia temperature-programmed desorption (NH3-TPD), and inductively coupled plasma-optical emission spectrometry (ICP-OES) analyses, revealing a regular hexagonal plate-like morphology and high surface area. H-ZSM-5 exhibited the largest surface area (248.2 m2/g) and total acidity (0.109 mmol NH3/g), while ion exchange slightly modified these properties. The catalytic system achieved excellent yields (up to 99 %) for various amines, demonstrating high efficiency and reusability. This study highlights the potential of zeolite-based catalysts as effective, recyclable materials for N-formylation processes.
Keywords: H-ZSM-5; Ion-Exchanged; N-Formylation; Formic Acid; Acidity